Ultrafast Sintering of Dense Li7La3Zr2O12 Membranes for Li Metal All‐Solid‐State Batteries - Faruk Okur; Huanyu Zhang; Julian F. Baumgärtner; Jaka Sivavec; Matthias Klimpel; Gregor Paul Wasser; Romain Dubey; Lars P.H. Jeurgens; Dmitry Chernyshov; Wouter vanBeek; Kostiantyn V. Kravchyk; Maksym V. Kovalenko (Advanced Science)
Abstract Ultrafast sintering (UFS) is a compelling approach for fabricating Li7La3Zr2O12 (LLZO) solid‐state electrolytes (SSEs), paving the way for advancing and commercializing Li‐garnet solid‐state batteries. Although this method is commonly applied to the sintering of LLZO ceramics, its use for producing dense, phase‐pure LLZO SSEs has thus far been primarily limited to millimeter‐thick pellets, which are unsuitable for commercial solid‐state batteries. This study presents ultrafast sintering as a highly effective approach for fabricating self‐standing, dense, 45 µm‐thick LLZO membranes. The chemical and structural evolution of LLZO membranes during the UFS process is characterized through in situ synchrotron X‐ray diffraction and thermogravimetric analysis‐mass spectrometry, complemented by an in‐depth investigation of surface chemistry using X‐ray photoelectron spectroscopy. The membranes in Li/LLZO/Li symmetrical cell configuration exhibit a high critical current density of up to 12.5 mA cm−2 and maintain superior cycling stability for 250 cycles at a current density of 1 mA cm−2, with an areal capacity limit of 1 mAh cm−2. The electrochemical performance of LLZO membranes is also assessed in full cell configuration using a pyrochlore‐type iron (III) hydroxy fluoride cathode.